A conceptual model of the impact of including carers in museum programmes for people with dementia. (November 2022) - Kinsey, Debbie; Orr, Noreen; Anderson, Rob; Lang, Iain
Background: Research has highlighted a need for more theoretical work in arts interventions, including the role of the dyad. This study aimed to test theories from a literature review on the impact of including carers in museum programmes for people with dementia, and develop a model which can be used in other programmes to consider the impact of including carers more broadly. Methods: Using a realist evaluation approach, theory was developed through interviews and participant-observation at six museums in the UK. Findings: The impacts of including carers fell into seven broad areas – caring responsibility, session function, controlling access, preventing engagement, comparisons and losses, long-term impact of in-the-moment activities, and reducing social isolation and opening up the museum. Conclusions: Including carers may have both unanticipated benefits and negative consequences, and greater attention is needed on how both carers and people with dementia can be supported in shared sessions. Carers should be viewed as participants of programmes, and can even be the main beneficiaries, even where the programme is ostensibly 'for' the person with dementia – it's not simply that carers are the enablers of, or barriers to, the impacts on the person with dementia.